META-ANALYSIS: THE INFLUENCE OF CONTEXTUAL TEACHING AND LEARNING APPROACHES ON MATHEMATICAL PROBLEM-SOLVING ABILITIES - Anggun Putri Handayani; Muhammad Fachri B. Paloloang; Baharuddin Baharuddin; Gandung Sugita (FKIP Universitas Muhammadiyah Tangerang, 2026)
Students' ability to solve mathematical problems remains a crucial issue in Indonesian education, often caused by a lack of contextual interaction and teacher-centered learning. This study aims to analyze the impact of the Contextual Teaching and Learning (CTL) approach on students' mathematical problem-solving abilities through a meta-analysis method. A total of 23 primary studies that met the inclusion criteria were analyzed using Comprehensive Meta-Analysis software version 4.0 with a random-effects model. The results show that the CTL approach has a strong and significant effect on students' mathematical problem-solving skills, with an overall effect size (Hedges’ g) of 0.819. Moderator analysis indicates that education level, region, and sample size do not significantly influence mathematical problem-solving ability through the CTL model. These findings affirm that the CTL approach is an effective instructional strategy for enhancing students' mathematical problemsolving abilities by connecting abstract concepts to real-world contexts. The educational implications of this study suggest that teachers and policymakers should consistently promote the implementation of CTL to foster more meaningful and contextual mathematics learning.